2014
DOI: 10.3389/fpsyt.2014.00007
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Inhibition of Return of Attention: Reduced Habituation to Threatening Faces in Schizophrenia

Abstract: Attention deficits are prominent among the core symptoms of schizophrenia. A recent meta-analysis has suggested that patients with schizophrenia have a deficit in endogenous disengagement of attention. In this research, we used a standard spatial cueing paradigm to examine whether the attention deficit of such patients is due to impaired attentional disengagement or defective novelty detection/habituation processes. In a spatial cueing procedure with peripheral non-predictive cues and a detection task, we mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…GABAergic interneuron dysfunction is also observed in mice lacking dysbindin Larimore et al, 2014), as well as in both the prefrontal cortex and hippocampus of schizophrenia patients (Benes and Berretta, 2001;Beasley et al, 2002;Hashimoto et al, 2003Hashimoto et al, , 2008Nakazawa et al, 2012). Second, impaired sensory habituation is a common manifestation in schizophrenia subjects (Geyer and Braff, 1987;Braff et al, 1992;Holt et al, 2005;Williams et al, 2013;Hu et al, 2014). In humans, sensory habituation defects are considered an intermediate, or "endo-"phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…GABAergic interneuron dysfunction is also observed in mice lacking dysbindin Larimore et al, 2014), as well as in both the prefrontal cortex and hippocampus of schizophrenia patients (Benes and Berretta, 2001;Beasley et al, 2002;Hashimoto et al, 2003Hashimoto et al, , 2008Nakazawa et al, 2012). Second, impaired sensory habituation is a common manifestation in schizophrenia subjects (Geyer and Braff, 1987;Braff et al, 1992;Holt et al, 2005;Williams et al, 2013;Hu et al, 2014). In humans, sensory habituation defects are considered an intermediate, or "endo-"phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, if landscape architecture stimuli can bias attention allocation, the psychological mechanisms underlying the attentional bias effect on landscape architecture remain unclear. Previous studies have demonstrated that the mechanisms of attentional bias and orienting cannot be considered as fully automatic (for a review see Santangelo and Spence, 2008 ), and further researches also adopted the spatial cueing paradigm and identified that there are two main components of attentional bias, faster orienting and delayed disengagement of attention ( Posner, 1980 ; Posner and Petersen, 1990 ; Vogt et al, 2008 ; Langley et al, 2011 ; Hu et al, 2014 ; Vromen et al, 2014 ; Harrison and Woodhouse, 2016 ), which correspond to early and later attentional processing, respectively. In this paradigm, participants need to judge whether the dot (target) is presented on the left or right side of the screen.…”
Section: Introductionmentioning
confidence: 99%
“…However, this hypothesis does not fit well with previously experimental results. Whether emotional, neutral faces or spiders are presented at the peripheral cueing locations, the magnitude of IOR effect have no conspicuous difference under all cue conditions ( Stoyanova et al, 2007 ; Lange et al, 2008 ; Hu et al, 2014 ), indicating that IOR is blind to emotion stimuli. Another special central cue-target paradigm presented supraliminal emotion cues at the center of the screen found that the attentional system tended to inhibit irrelevant negative emotion but not inhibit irrelevant positive emotion ( Chao, 2010 ).…”
Section: Introductionmentioning
confidence: 94%